Dynamics of life quality of children with cerebral palcy by influence of occupational therapy and physical therapy - Kyshchenko О. O.; Lazarieva О. B. (Journal of Education, Health and Sport, 2018)
The level and potential of improving life quality of children with cerebral palsy (CP), as well as the impact of occupational therapy and physical therapy on them, is an actual subject of the study. The quality of life of children with CP is a complicated social problem, the value of which does not decrease in the adult age of patients. The purpose: to assess the dynamics of life quality of children with CP under the influence of rehabilitation programs. Material and methods: 106 patients (54 with spastic hemiplegia HP and 52 with spastic diplegia DP) aged from 4 to 6 years were examined in accordance with CPQOL-Child, GMFCS and МАСS. Examined children of HP and DP groups have been divided into main and control subgroups each. Control subgroups passed the standard program of occupational therapy and physical therapy. Results: among the children with CP in HP group in accordance with GMFCS the level II was 25% of children, the level III - 50%, IV – 25 %; and in DP group - 11,1 %, 33,3 % and 57,2 % children respectively. Among the children in HP group in accordance with МАСS the level II was 7,1 % of children, the level III – 57,2%, IV – 35,7 %; %; and in DP group - 22,2 %, 66,7 % and 11,1 % children respectively. Under the influence of rehabilitation course in groups of children there were significant improvements in most of the domains of life quality. Only "Social well-being and acceptance", "Family health" have not changed in all groups (p> 0,05). In addition, the most reliable results in the main groups were identified by the "Functioning" domain (p <0,05). Conclusions: means of ocupational therapy and physical therapy are effective in improving the life quality of children with CP. Their rational choice, combination and proper organizational and methodological support can improve program outcomes.